The Synthesis of Cyclodextrin Derivatives with Ethilenic Bond and Their Application on Silk - 方熙 黄良晨 赵曙辉 黄芳 (东华大学学报(英文版), 2011)
The cyclodextrin （CD） derivatives with ethilenic bonds mono-（2-O-tosyl）-6-acryloyl-β-cyclodextrin （β-CD-2-OTs-6-A） and 6-acryloyl-β-cyclodextrin （β-CD-6-A） were respectively synthesized. β-CD-2-OTs-6-A was prepared by the reaction propylene chloride with β-CD-2-OTs. β-CD-6-A was synthesized by the reaction propylene chloride with β-CD. The most suitable pH value for β-CD-6-A grafted onto silk fabric was proved to be 5. The optimal condition for grafting β-CD-2-OTs-6-A onto silk was proved： monomer concentration of 20% on weight of fabric（o.w.f）, potassium persulfate of 1.85% o.w.f, liquor ratio of 1∶50, pH=5, and treated 30 min at 80 ℃. Compared with β-CD-6-A, the grafting reaction has a higher graft yield while β-CD-2-OTs-6-A acts as the monomer.